„Moment elegijny” Victora Hugo - Siwiec, Magdalena (Poznańskie Studia Polonistyczne. Seria Literacka, 2011)
This article attempts to define the place of elegiac modality in the literary output of Victor Hugo. The starting point for the discussion and at the same time appropriate interpretative tool is the definition of elegy derived from the writings of German theoreticians of Romanticism: Friedrich Schiller and Friedrich Schlegel. The thing is question is the elegiac attitude based on exposing of what is ideal and lost at the same time. The above, indeed, constitutes an answer to the questions of the experience of crisis so inherent to Romanticism. Analyses of the early poetical volumes written by the author show a particular evolution of Hugo’s conception of poetry. Politically committed The Odes, being anti-elegiac by assumption, are discussed, as well as purely poetical Eastern poems overtly promoting limitless freedom which characterizes the creative imagination. The interpretation of individual poems from these volumes proves, however, that one can discern a certain elegiac tone in them, though the tone is never dominant. The volume that distinctively enhances the elegy (thus far discredited by Hugo and from then on permanently occurring in his works) turns out to be Autumn Leaves — a collection of poems of contemplative, melancholic, visionary and self-reflective character.